Genomic analyses of pneumococci reveal a wide diversity of bacteriocins – including pneumocyclicin, a novel circular bacteriocin - Bogaardt, Carlijn (BMC Genomics, 2015)
BACKGROUND: One of the most important global pathogens infecting all age groups is Streptococcus pneumoniae (the ‘pneumococcus’). Pneumococci reside in the paediatric nasopharynx, where they compete for space and resources, and one competition strategy is to produce a bacteriocin (antimicrobial peptide or protein) to attack other bacteria and an immunity protein to protect against self-destruction. We analysed a collection of 336 diverse pneumococcal genomes dating from 1916 onwards, identified bacteriocin cassettes, detailed their genetic composition and sequence diversity, and evaluated the data in the context of the pneumococcal population structure. RESULTS: We found that all genomes maintained a blp bacteriocin cassette and we identified several novel blp cassettes and genes. The composition of the ‘bacteriocin/immunity region’ of the blp cassette was highly variable: one cassette possessed six bacteriocin genes and eight putative immunity genes, whereas another cassette had only one of each. Both widely-distributed and highly clonal blp cassettes were identified. Most surprisingly, one-third of pneumococcal genomes also possessed a cassette encoding a novel circular bacteriocin that we called pneumocyclicin, which shared a similar genetic organisation to well-characterised circular bacteriocin cassettes in other bacterial species. Pneumocyclicin cassettes were mainly of one genetic cluster and largely found among seven major pneumococcal clonal complexes. CONCLUSIONS: These detailed genomic analyses revealed a novel pneumocyclicin cassette and a wide variety of blp bacteriocin cassettes, suggesting that competition in the nasopharynx is a complex biological phenomenon. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1729-4) contains supplementary material, which is available to authorized users.